June zero [videorecording (DVD)] - Paltrow, Jake, 1975-; Shoval, Tom; Scharf, Yaron, 1963-; Levy, Eytan; Gil-Efrat, Ayelet; Shuki, Inbal; Grad, Tsaḥi; Levi, Ydav; Hagy, Tom; Smolarchik, Ami (Contemporary classics (Cohen Media Group), 2024)
The 1961 trial of Adolf Eichmann, a principal architect of the Holocaust, is revisited in a gripping and surprising new vision from American filmmaker Jake Paltrow. Based on true accounts, June Zero is told from the unique perspectives of three distinct figures: Eichmann's Jewish Moroccan prison guard; an Israeli police investigator who also happens to be a Holocaust survivor and a precocious and clever 13-year-old Libyan immigrant. Entirely shot on 16mm film, Paltrow's vividly textured work brings to life the varied experiences of these characters, emphasizing that the same historical events are often perceived differently by people around the world. June Zero underscores the notion that shared traumas have the power to forge the strongest bonds and give rise to unexpected moments of triumph and connection. As the film delves into the complexities of the human experience during this pivotal trial, it serves as a poignant reminder that history's impact can be both diverse and unifying.